The Archipelago of Us - Schipp, Reneé (Curtin University, 2019)
The Archipelago of Us is the culmination of the author’s lived experience of the excised world of Christmas Island and the Cocos (Keeling) Islands. Through a combination of bearing witness, interviews and research, the author takes the reader on a classic quest journey. This creative work examines the way in which these communities challenge us to think more broadly about what it means to be Australian, and asks at whose expense our national identity is forged.